Pemetaan Kebisingan Pada Area Kegiatan Pembangunan Gedung Asrama Mahasiswa Nusantara Menggunakan Zona Kontur - Okik Hendriyanto Cahyonugroho; Septi Ika Nurfadila (Prosiding ESEC, 2023)
Keeping the community comfortable while developing is very important and needs to be considered. Besides climate and air quality, another thing that must be considered is noise level. One of them is in Pasar Minggu, South Jakarta in the construction of Nusantara Student Dormitory Building. This journal aims to model the noise level as a reference material for the health of workers in the activity environment and calculate compensation to the local government or community due to the noise caused. To achieve this goal, the classification of points and sampling time is carried out. Each parameter affects the noise measured in dB. The parameter that most affects the presence of many activities in that period is the one with the highest weight. Then, in the form of noise contour modeling, the values of several parameters were analyzed. The results of the modeling show that at the location of the construction activities of the dormitory building there are several periods of time in which the weight of the noise exceeds the quality standard. The result of the highest Leq average measurement is 59.7 dB obtained at 17.00-22.00 WIB, while the highest Ls value is obtained from the 3rd sampling point of 60.4 dB. From the data, it is known that the noise level exceeds the quality standard set for residential areas. The standard set is 55 dB based on the Decree of the Minister of Environment No. 48/MENLH/11/1996.